Evaluation of the Clinical Performance of Nurses Employed in the Neonatal Intensive Care Units - Amiri Simkoii, Fateme; Masoumpoor, Anahita; Shirinabadi-Farahani, Azam; Pahlevanzadeh, Bagher (Advances in Nursing & Midwifery, 2019)
Introduction: Nurses are as the most important health care providers who require extensive knowledge and skills in this field. Despite the high importance of the issue, our knowledge of the current status of clinical performance and levels of nursing skills in the neonatal intensive care units is very low. The present study was done with the aim of determining the status of clinical performance of neonatal nurses in the NICU. Methods: The present research is a descriptive study, through which the clinical performances of 96 neonatal nurses were observed in eight areas. Data collection was done using a researcher-made Scale. The data were analyzed with SPSS version 21. Results: The neonatal nurses’ clinical performances were acceptable (69.74%) in all the areas which includes vital signs control, daily cares, respiratory cares, infants feed, vessels’ access, medicine prescription, phototherapy and using required equipment for neonates (such as warmer, Infusion pump, Defibrillator, Incubator, Ventilator and Phototherapy).The highest and lowest practices were assessed in the fields of infant nutrition (84.11%) and equipment utilized (51.93%), respectively. Conclusions: The nursing skills in the study areas seems within an acceptable range, which could be due to the NICU nurses’ interests in this field. In order to improve the performance of nurses in areas where there is a weakness, we suggest considering the importance of these care and disadvantages due to negligence.